The Development Instructional Media Pop-Up Art Book with Internal Stand Mechanism Technique on Early Chilhood Recognizing Concept - Zinnurain, Zinnurain; Suhardi, Muhammad; Najwa, Lu'luin (UNDIKMA, 2024)
This research is research and development with the aim of developing instructional media Pop-Up Art Book with internal stand mechanism on early chilhood recognizing concept in Smart Eduplay Institute, Terong Tawah, Labuapi District, West Lombok Regency, West Nusa Tenggara. with 15 respondents. The approach on the research is instructional development with class and product oriented. The research method refers to the development of the J. Moonen and Rowntree prototype model. Learning evaluation is carried out in stages, such as a review by experts consisting of learning design experts, material experts, and learning media experts, and followed by face-to-face and large group trials. Formative evaluation was carried out to obtain learning outcomes from pretest and posttest. Reviews shown that the quality of learning media is in the â€œvery goodâ€ category, on average 3,30. Trial result in â€œvery goodâ€ category, on average 3,41. Trial product effectiveness shown pretest average is 52,76 and posttest average is 82,07. The average range is 29,3. Therefore, developing instructional media Pop-up Art Book with internal stand mechanism on early chilhood recognizing concept makes a positive contribution in achieving learning goals optimally